From border of the walled city to conventual and hospital citadel - Capano, Francesca (Eikonocity. Storia e Iconografia delle Città e dei Siti Europei, 2018)
From the fifteenth century the hermits of Pietro from Pisa order settled in the edge of Naples between the acropolis and the northern walls, these contributed to give this area a conventual vocation to this area. In 1519 the Incurabili hospital was also established by Maria Lorenza Longo, who came from Spain. In this urban area, included between Pisanelli street (Decumano Superior), San Gaudioso alley, Maria Longo street and Luciano Armanni street, there are a lot of religious buildings and a hospital, among which we point out the convent of Santa Maria Regina Coeli.. Where the historical and artistic characters of Renaissance and Late Baroque manifested intensely. The preservation of this urban monument is very compromised: unconditional reuse for the development of the hospital area caused the abandon or changes of churches. In the best example monasteries and churches have turned into schools, universities, classrooms and libraries, modifying the recognition of very significant monuments.